Radikalisme Agama Legitimasi Tafsir Kekerasan di Ruang Publik - Musa Rumbaru; Hasse J (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Religious radicalism shows a high intensity over the last decade in Indonesia. This religious radicalism subsequently brings a massive impact when it is admitted by the action of choosing violence as the only way. In this article, we put forward our arguments: first, the point of intersection between violence and religion; second, radicalism used as a method to respond to various issues such as injustice, and so on. Third, regarding alternative methods that can be done in order to minimize radical action and understanding in Indonesia. This paper confirms three main points. First, the teaching of religion, especially Islam basically contains the peace teachings and safety; therefore, one was very anti-violence and radical actions. Second, radical action can be a method to hear our voices in response to various injustices that occur in a few places in the world. Third, understand the narrowly religious texts have an impact on building understanding and narrow action anyway.